Glycogen supercompensation in skeletal muscle after cycling or running followed by a high carbohydrate intake the following days: a systematic review and meta-analysis - Solem, K.; Clauss, M.; Jensen, J. (Frontiers in Physiology, 2025)
Introduction: Bergström and Hultman demonstrated that exhaustive exercise depleting muscle glycogen followed by three days on a carbohydrate-rich diet resulted in a doubling of the glycogen content. Although many studies have confirmed this finding, the magnitude of glycogen supercompensation and the mechanisms behind elevated glycogen content after exercise remain unclear. This systematic review meta-analyzed investigations on muscle glycogen supercompensation after exercise and 3-5 days on a high-carbohydrate diet. Meta-regression analyses were conducted to explore the influence of specific variables on muscle glycogen supercompensation.